Terminy „sansara” i „nirvana” kak âzykovye sredstva opisaniâ kartiny mira v filosofskoj tradicii mahaâny - Belâkov Aleksej О. (Stylistyka, 2020)
The article deals with the fundamental concepts of Buddhism – samsara and nirvana, explains their etymology, and application in the philosophy of Mahayana Buddhism. At the end of the article, the author draws conclusions about the need to differentiate the general and particular applications of these concepts in comparative studies on religion, as well as about the variability and heterogeneity of approaches to the consideration of the Buddhist worldview within the Buddhist traditions.